2007
DOI: 10.1007/s10803-007-0502-1
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits and Cognitive Performance in Young People with Mild Intellectual Impairment

Abstract: Cognitive performance and the relationship between theory of mind (TOM), weak central coherence and executive function were investigated in a cohort of young people with additional learning needs. Participants were categorized by social communication questionnaire score into groups of 10 individuals within the autistic spectrum disorder (ASD) range, 14 within the pervasive developmental disorder range and 18 with few autistic traits. The ASD group were significantly poorer than the other groups on a test of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The present patients suffered problems of communication, social interaction, behavior, and showed some of the classic stereotypes of autistic spectrum disorders, but the most prominent manifestation was a global and severe neurodevelopmental disorder affecting cognition and motor function. It has been described that 30%–50% of patients with developmental delay or mental retardation have different types of associated neuropsychiatric symptoms, including autistic features [Harris et al., ]. Therefore, the present patients might be described as being affected by a neurodevelopmental disease that involves different signs: psychomotor delay, epileptic activity, and features of autism.…”
Section: Discussionmentioning
confidence: 84%
“…The present patients suffered problems of communication, social interaction, behavior, and showed some of the classic stereotypes of autistic spectrum disorders, but the most prominent manifestation was a global and severe neurodevelopmental disorder affecting cognition and motor function. It has been described that 30%–50% of patients with developmental delay or mental retardation have different types of associated neuropsychiatric symptoms, including autistic features [Harris et al., ]. Therefore, the present patients might be described as being affected by a neurodevelopmental disease that involves different signs: psychomotor delay, epileptic activity, and features of autism.…”
Section: Discussionmentioning
confidence: 84%
“…Four studies using the Behavioral Assessment of the Dysexecutive Syndrome reveal mixed findings. Although Hill and Bird (2006) found executive control deficits on the Behavioral Assessment of the Dysexecutive Syndrome in a group of high-functioning adults, Rajendren and colleagues (2005) and Harris and colleagues (2008) failed to find deficits on the Behavioral Assessment of the Dysexecutive Syndrome in adolescents with autism, and Boucher and colleagues (2005) found intact performance on the Zoo Map subtest of the Behavioral Assessment of the Dysexecutive Syndrome in young adults with autism. Results from the Predicaments Test (Channon et al, 2001), another ecologically valid executive control task, have been reported in a study of adolescents with autism.…”
Section: Autism Performance On New Tasks Claiming Verisimilitudementioning
confidence: 94%
“…The way a person implements a solution or group of solutions could be part of his/her personal preference, a coordination trait that can distinguish this person from others. Effects of personal traits on motor coordination have been studied typically in populations with neurological or psychological abnormalities such as autism, dyspraxia, developmental coordination disorder, and others (Harris et al 2008; Lingham et al 2010; Cheng et al 2017; Curioni et al 2017). Personality traits such as risk taking, novelty seeking, reward dependence, general arousal, and fear of falling have been linked to cerebellar activity (Picerni et al 2013; Petrosini et al 2015) and are known to correlate with indices of performance (Miller and Saygin 2013; Zaback et al 2015).…”
Section: Introductionmentioning
confidence: 99%